Dislocation density in cellular rapid solidification using phase field modeling and crystal plasticity. (January 2022) - Lindroos, Matti; Pinomaa, Tatu; Ammar, Kais; Laukkanen, Anssi; Provatas, Nikolas; Forest, Samuel
Highlights: Phase field and crystal plasticity coupled in rapid solidification. Solute segregation induce heterogeneous dislocation density distribution. Segregation cells and segregation pools localize dislocations and residual stresses. Abstract: A coupled phase field and crystal plasticity model is established to analyze formation of dislocation structures and residual stresses during rapid solidification of additively manufactured 316L stainless steel. The work focuses on investigating the role of microsegregation related to the intra-grain cellular microstructure of 316L. Effect of solidification shrinkage is considered along with dislocation mediated plastic flow of the material during solidification. Different cellular microstructures are analyzed and the characteristics of the cell core, boundary and segregation pools are discussed with respect to heterogeneity of dislocation density distributions and residual stresses. Quantitative comparison with experimental data is given to evaluate the feasibility of the modeling approach.